The biology and culture of marine bivalve mollucs of the genus Anadara - Broom, M. J. (International Center for Living Aquatic Resources Management, 1985)
The review is made of the general biology, ecology, population dynamics, reproduction and culture methods of marine bivalves of the family Arcidae, subfamily Anadarinae.